How much do infrastructural investments mitigate impacts of seasonal shocks on food security? - Henry Kankwamba; Lukas Kornher (University of Bonn, Center for Development Research (ZEF), 2019)
Ending extreme hunger requires the interaction of both household and community level infrastructural investments. When communities and households are capital infrastructure constrained, the effects of extreme events such as droughts can fetter consumption growth and food security. This paper, assesses the impact of seasonal weather shocks on food security conditional on access to public physical infrastructure. The study uses fixed effects regression techniques on representative Malawian panel data collected between 2010 and 2016. The study uses three key indicators of food security namely food consumption expenditure shares, the Berry Index of dietary variety, and the Shannon Entropy Index. To measure idiosyncratic and covariate shocks, self-reported survey data and high-resolution station based standardized precipitation - evapotranspiration index were used. To measure infrastructure, survey data, triangulated with remote sensed night time lights, were used to construct an infrastructure index in a logistic regression framework. Results show that assuming minimal infrastructure a standard deviation deficit in the one to three-month interval drought reduces consumption by 26%. Assuming normal historical weather conditions, infrastructure improves economic access to food by 15%. Thus, conditional on infrastructure, the impacts of extreme weather events on food security are reduced by 54%.
Keywords: Q12; D13; D15; 330; Food security; Dietary Diversity; Idiosyncratic and covariate shocks; infrastructure; Standardized Precipitation - Evapotranspiration Index; Night Time Lights